Systemic approach for optimizing information technology resource as a contribution of information system governance - Noureddine Falih; Brahim Jabir; Khalid Rahmani (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Information technology (IT) resource management is considered as one of the main pillars of Information System (IS) governance in the company. In this article, we propose a systemic approach from the structural paradigm based essentially on the formal extension of the ISO 19440 Meta-model. This structure contains specific constructs from the Cobit framework and system tools as the Galois lattices, likely to bring a better vision of the use of IT resource in the company. This technique allows a systemic analysis applied to special structural matrices to evaluate the deployment mode of IT resource to achieve business processes. Such approach allows a good optimization of IT resource as a pragmatic and effective contribution to Information System governance.